2013
DOI: 10.1159/000350918
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen-Induced Autophagy Signaling in Innate Immunity

Abstract: Innate immunity induces rapid responses to fight invading pathogens. To eliminate intracellular bacteria or viruses, innate cellular responses lead to the production of nuclear factor-κB-dependent inflammatory cytokines, inflammasome activation, type I interferon synthesis, and/or eventually death of the infected cells. Autophagy emerged as another component of innate immunity, as it offers an immediate autonomous cell defense mechanism by degrading intracellular pathogens. In addition, autophagy participates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 132 publications
(185 reference statements)
0
22
0
Order By: Relevance
“…LPS, a major component of the outer membrane of Gram-negative bacteria, has been recently considered as a critical stimulus of adipose tissue inflammation and a regulator of autophagy. LPS has been known to bind TLR2 and TLR4 on the plasma membrane with the involvement of MD-2 to activate an immune response and induce inflammation (60). The data from human studies has shown that obese subjects have altered gut microflora, leading to the elevation of circulating LPS (61).…”
Section: Discussionmentioning
confidence: 99%
“…LPS, a major component of the outer membrane of Gram-negative bacteria, has been recently considered as a critical stimulus of adipose tissue inflammation and a regulator of autophagy. LPS has been known to bind TLR2 and TLR4 on the plasma membrane with the involvement of MD-2 to activate an immune response and induce inflammation (60). The data from human studies has shown that obese subjects have altered gut microflora, leading to the elevation of circulating LPS (61).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy not only is a regulated catabolic process but also plays an essential role in other signal pathways such as apoptosis and innate immunity (47)(48)(49). As NDV induced apoptosis and host immune response in vitro and in vivo, it is reasonable to conclude that autophagy might affect NDV replication through regulation of other pathways.…”
Section: Figmentioning
confidence: 99%
“…In addition, autophagy emerges as a component of innate immunity as it can destroy infectious viruses or viral components essential for viral replication or assembly, a process referred to as virophagy, linking virus detection to antiviral innate immune signals or participating in the regulation of immune and inflammatory cell response [107,108]. In this circumstance, HDAC6 facilitates aggresome formation and autophagic degradation for the clearance of intracellular invasive viruses or viral proteins.…”
Section: Controlling Antiviral Immune Responsesmentioning
confidence: 99%